Administration of a Probiotic Mixture Ameliorates Cisplatin-Induced Mucositis and Pica by Regulating 5-HT in Rats. (16th September 2021) - Wu, Yuanhang; Wu, Jianlin; Lin, Zhikun; Wang, Qian; Li, Ying; Wang, Aman; Shan, Xiu; Liu, Jiwei
Abstract : Probiotic-based therapies have been shown to be beneficial for chemotherapy-induced mucositis. Previous research has demonstrated that a probiotic mixture ( Bifidobacterium brevis, Lactobacillus acidophilus, Lactobacillus casei, and Streptococcus thermophilus ) can ameliorate chemotherapy-induced mucositis and dysbiosis in rats, but the underlying mechanism has not been completely elucidated. We aimed to determine the inhibitory effects of the probiotic mixture on cisplatin-induced mucositis and pica and the underlying mechanism, focusing on the levels of 5-hydroxytryptamine (5-HT, serotonin) regulated by the gut microbiota. A rat model of mucositis and pica was established by daily intraperitoneal injection of cisplatin (6 mg/kg) for 3 days. In the probiotic+cisplatin group, predaily intragastric injection of the probiotic mixture (1 × 10 9   CFU / kg BW) was administrated for 1 week before cisplatin injection. This was then followed by further daily probiotic injections for 6 days. Histopathology, pro-/anti-inflammatory cytokines, oxidative status, and 5-HT levels were assessed on days 3 and 6. The structure of the gut microbiota was analyzed by 16S rRNA gene sequencing and quantitative PCR. Additionally, 5-HT levels in enterochromaffin (EC) cells (RIN-14B cell line) treated with cisplatin and/or various probiotic bacteria were also determined. The probiotic mixture significantly attenuated kaolin consumption, inflammation, oxidative stress, and the increase in 5-HT concentrations in rats with cisplatin-induced intestinal mucositis and pica. Cisplatin markedly increased the relative abundances of Enterobacteriaceae_other, Blautia, Clostridiaceae_other, and members of Clostridium clusters IV and XIVa. These levels were significantly restored by the probiotic mixture. Importantly, most of the genera increased by cisplatin were significantly positively correlated with colonic 5-HT. Furthermore, in vitro, the probiotic mixture had direct inhibitory effects on the 5-HT secretion by EC cells. The probiotic mixture protects against cisplatin-induced intestine injury, exhibiting both anti-inflammatory and antiemetic properties. These results were closely related to the reestablishment of intestinal microbiota ecology and normalization of the dysbiosis-driven 5-HT overproduction.